Orientalist and Nonbeliever Criticism of the Qirā'āt of the Qur'an: Analysis and Response in the Book Al-Qirā'āt fī Naẓari al-Mustashriqīn wa al-Mulḥidīn - Indika Ilwan Wahilmi; Hafidh Dinul Kholis; Diana Lum'ah (Quranic and Tafsir studies Programme at Ushuluddin Faculty, 2025)
This article offers a novel analytical examination of ʿAbd al-Fattāḥ al-Qāḍī’s methodological response to orientalist and nonbeliever critiques of Qur’anic qirāʾāt, an area that previous studies have addressed only descriptively without engaging the epistemological structure underlying classical Muslim scholarship. Addressing this research gap, the study analyses al-Qāḍī’s triadic criteria of qirāʾāt authenticity conformity to the ʿUthmānic rasm, linguistic coherence, and continuous transmission and demonstrates how these principles systematically counter key claims advanced by Goldziher, Jeffery, Nöldeke, Ibn Warraq, and Luxenberg. The findings reveal that orientalist critiques rest on manuscript-centric assumptions derived from Biblical textual criticism, whereas nonbeliever critiques rely on a priori skepticism toward oral transmission. By showing that canonical qirāʾāt constitute a disciplined form of linguistic plurality rooted in prophetic instruction rather than textual instability, this study offers a clear methodological model for assessing modern critiques of Qur’anic textuality. The article contributes to contemporary Qur’anic studies by bridging sanad-based epistemology with current debates in manuscript research and by clarifying the conceptual categories often conflated in Western scholarship.